2019
DOI: 10.1111/ans.15033
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with laparoscopic and robotic surgery for the treatment of periampullary tumours: single institution experience with the first 30 consecutive cases

Abstract: Background: Concerns have been raised about the safety of minimally invasive surgery (MIS) for pancreatoduodenectomy (PD) during the early learning phase. In this study, we present our initial experience with MIS for periampullary tumours. Methods: Retrospective review of the first 30 consecutive patients who underwent laparoscopic (LS)/robotic surgery (RS) for periampullary tumours between 2014 and 2017. Results: Twenty-seven patients underwent PD, including three total pancreatectomies (TPs) and three underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 33 publications
1
32
0
1
Order By: Relevance
“…Despite this being our early experience, we found RBS to be safe and feasible as evidenced by the absence of open conversions or mortality and the low morbidity rate. Nonetheless, it is important to highlight, that we had concomitant experience with a high volume of major laparoscopic and robotic HPB surgery during the study period [3][4][5]31 which would have partially accounted for our favourable outcomes and relatively short learning curve. Although it is widely reported that robotic surgery allows 'open' surgeons to transition more quickly to MIS compared to laparoscopy with shorter learning curve, in our experience the learning curve for experienced laparoscopic surgeons is even shorter.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite this being our early experience, we found RBS to be safe and feasible as evidenced by the absence of open conversions or mortality and the low morbidity rate. Nonetheless, it is important to highlight, that we had concomitant experience with a high volume of major laparoscopic and robotic HPB surgery during the study period [3][4][5]31 which would have partially accounted for our favourable outcomes and relatively short learning curve. Although it is widely reported that robotic surgery allows 'open' surgeons to transition more quickly to MIS compared to laparoscopy with shorter learning curve, in our experience the learning curve for experienced laparoscopic surgeons is even shorter.…”
Section: Resultsmentioning
confidence: 99%
“…In our experience, robotic surgery enhances the individual capabilities of a laparoscopic surgeon allowing him/her to perform even more complex tasks such as difficult fine suturing which he would otherwise be less comfortable with. 4,25,31 The main barrier to the widespread use of robotic surgery today is the increased cost associated with the procedure resulting in limited access to both patients and surgeons to the technology. 4 Due to the high cost of purchasing and for maintenance of the robot; few surgeons worldwide have regular access to this technology for training.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations